Analysis of Learning Styles in F7 Phase Students of Informatics at SMAN 4 Surakarta Using Felder and Solomon Theory - Kusumaningrum, Nidha; Mariono, Dwi; Waskito, Adi (Politeknik NEST, 2024)
This research examines the learning preferences of F7 phase students at SMAN 4 Surakarta in Informatics, utilizing the Felder-Solomon model. Findings indicate that a large proportion of students (96%) predominantly prefer visual learning, with significant tendencies towards active (74%), sensing (89%), and sequential (59%) learning styles. These results have important implications, suggesting that teachers can devise more effective educational strategies by integrating interactive, visual, and well-structured methods. Moreover, employing varied instructional approaches is essential to cater to the diverse learning styles of students. Gaining a thorough understanding of the students' learning style distribution enables the creation of an optimal learning environment tailored to individual needs and supports the development of strategies that significantly improve student engagement and academic performance.